2014
DOI: 10.1590/s0036-46652014000500013
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Beta-1a Treatment in HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis: A Case Report

Abstract: Here a young patient (< 21 years of age) with a history of infective dermatitis is described. The patient was diagnosed with myelopathy associated with HTLV-1/tropical spastic paraparesis and treated with interferon beta-1a. The disease was clinically established as HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), and laboratory tests confirmed the presence of antibodies to HTLV-1 in the cerebrospinal fluid (CSF). Mumps, cytomegalovirus, Epstein-Barr virus, schistosomiasis, herpes virus 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…On the other hand, our study also reveals another parallel between neuroinflammatory disorders HAM/TSP and multiple sclerosis, namely their unique sensitivity to IFN-β over IFN-α. Of note, our results provide mechanistic evidence for the previously described immunovirological and clinical impact observed in vivo with IFN-β therapy in HAM/TSP patients, in an open-label trial (Oh et al, 2005 ), as well as two case reports with remarkable clinical response (Costa et al, 2012 ; Viana et al, 2014 ). This superior antiproliferative effect of IFN-β in HAM/TSP, as compared to IFN-α, parallels our findings in the other major HTLV-1-associated disease, Adult T-cell Leukemia (Dierckx et al, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, our study also reveals another parallel between neuroinflammatory disorders HAM/TSP and multiple sclerosis, namely their unique sensitivity to IFN-β over IFN-α. Of note, our results provide mechanistic evidence for the previously described immunovirological and clinical impact observed in vivo with IFN-β therapy in HAM/TSP patients, in an open-label trial (Oh et al, 2005 ), as well as two case reports with remarkable clinical response (Costa et al, 2012 ; Viana et al, 2014 ). This superior antiproliferative effect of IFN-β in HAM/TSP, as compared to IFN-α, parallels our findings in the other major HTLV-1-associated disease, Adult T-cell Leukemia (Dierckx et al, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…Type I IFNs, including IFN-a and IFN-b, have been used for the treatment of HTLV-1-associated diseases (32,33), suggesting the important role of type I IFNs in HTLV-1 infection. Our findings demonstrated that Ku70 positively regulated HTLV-1-induced IFN-b production.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous uptake of low-doses of prednisolone by TSP/HAM patients improved their Osame Motor Disability Score both in short-term (less than 3 years) and long-term (more than 3 years) durations of treatment, in comparison to untreated TSP/HAM patients. Because corticosteroid treatments are neither efficient nor tolerated by some patients, alternative treatments using molecules with anti-inflammatory properties, such as cyclosporine A [ 189 ], pentoxifylline [ 190 ], danazol [ 191 ], or antiviral cytokines, such as IFN-α [ 192 , 193 ] or IFN-β [ 194 ], have been developed among others [ 195 ]. Aside from the general motor disability, other TSP/HAM-associated symptoms, such as spasticity, bladder dysfunctions, urinary tract infections, constipation, neuropathic and mechanical pains or erectile troubles are subject to a wide array of drugs [ 123 ].…”
Section: Htlv-1 Treatment and Drug Developmentmentioning
confidence: 99%